Mengembangkan Sosial Emosional Anak Usia Dini Melalui Bermain - Ijar Salna; Lu’lu Rahmadanti; Nur Sa’adah; Fatimah Fatimah; Khadijah Khadijah; Hairani Ananda Putri (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
Playing is an activity that is very important for children's growth and development. Playing must be carried out on the child's own initiative, playing in a fun way provides a learning process for the child. Playing can also stimulate various things in children's development, such as physical movement, cognitive, mathematical logic, language, moral-religious, socio-emotional and artistic. Through play, children's creativity will awaken and develop optimally. Child and socio-emotional development: In principle, children learn through social interactions, both with adults and peers. Social development has a positive impact on children's growth and development. Social development supports communication skills, academic success and school adjustment, strengthens peer relationships, and creates a positive learning environment. Therefore, this skill must be developed optimally from an early age. Playing is one way to develop social-emotional skills in childhood. Play can be used as an alternative means to improve social and emotional development in children.